Legal Analysis of Coal Mining in Efforts to Maintain The Environmental Sustainability - Irawan, Iwan (Humaniora, 2016)
The goal of this article was to suggest the government to make the appropriate laws and policies in order to optimize the utilization of coal based on environmental sustainability. The research applied library research from several research results and the Act no. 4 of 2009. Data were analyzed qualitatively by the way of decomposition, connecting with the rules, and the legal experts? opinion. It can be concluded that investors are not optimal in managing and conserving the coal mining and the government has not standaridized the environmental management.